Development of measurement scale for functional congruity in guest houses. (October 2018) - Wang, Sha; Hung, Kam; Li, Minglong
Abstract: The rapid development of guest houses in China intensified business competition. Understanding the experiences and expectations of customers can help guest houses gain advantage over competitors when customers are particular about their accommodation experience. Given the limited discussions, only a few systematic approaches were developed for the functional needs of customers toward guest houses. Thus, the present study developed a measurement scale for the functional congruity of guest houses based on the procedures recommended by Churchill (1979). The scale was tested, which was found reliable and valid. Marketing implications were provided theoretically and practically based on the results. Highlights: Guest houses are unique in terms of customers' needs and expectations. Functional congruity is essential for understanding tourist decision making. Functional congruity of guest houses in China includes 5 dimensions. This study operationalized functional congruity of guest houses and carries implications for management practice. The scale developed lays the foundation for future research.